2011
DOI: 10.3324/haematol.2010.026138
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA characterize genetic diversity and drug resistance in pediatric acute lymphoblastic leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundMicroRNA regulate the activity of protein-coding genes including those involved in hematopoietic cancers. The aim of the current study was to explore which microRNA are unique for seven different subtypes of pediatric acute lymphoblastic leukemia. Design and MethodsExpression levels of 397 microRNA (including novel microRNA) were measured by quantitative real-time polymerase chain reaction in 81 cases of pediatric leukemia and 17 normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
193
1
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(214 citation statements)
references
References 42 publications
8
193
1
12
Order By: Relevance
“…Most striking differences were found for 11q23/ MLL-rearranged precursor B-ALL cases, which displayed downregulation of miR-708 and upregulation of miR-196b and t(12;21)/TEL-AML1-positive precursor B-ALL cases, which distinguished by upregulation of miR-383, miR-125b, miR-99a and miR-100 (Table 1). 22 Remarkably, the miRNA signature of TEL-AML1-positive and hyperdiploid (450 chromosomes) ALL cases partly overlapped similar to what has been observed for mRNA expression profiles, 22,29 which may suggest a common underlying biology. High expression of miR-33, miR-215, miR-369-5p, miR-496, miR-518d and miR-599 was associated with an unfavorable prognosis whereas high expression of other miR-genes (that is, miR-10a, miR-134, miR-214, miR-484, miR-572, miR-580, miR-624 and miR-627) was linked to a favorable prognosis in pediatric ALL.…”
Section: Aberrant Mirna Expression Characterizes Different Cytogenetimentioning
confidence: 50%
See 3 more Smart Citations
“…Most striking differences were found for 11q23/ MLL-rearranged precursor B-ALL cases, which displayed downregulation of miR-708 and upregulation of miR-196b and t(12;21)/TEL-AML1-positive precursor B-ALL cases, which distinguished by upregulation of miR-383, miR-125b, miR-99a and miR-100 (Table 1). 22 Remarkably, the miRNA signature of TEL-AML1-positive and hyperdiploid (450 chromosomes) ALL cases partly overlapped similar to what has been observed for mRNA expression profiles, 22,29 which may suggest a common underlying biology. High expression of miR-33, miR-215, miR-369-5p, miR-496, miR-518d and miR-599 was associated with an unfavorable prognosis whereas high expression of other miR-genes (that is, miR-10a, miR-134, miR-214, miR-484, miR-572, miR-580, miR-624 and miR-627) was linked to a favorable prognosis in pediatric ALL.…”
Section: Aberrant Mirna Expression Characterizes Different Cytogenetimentioning
confidence: 50%
“…[18][19][20][21] Quantitative analysis of 397 miRNAs revealed that leukemic cells of pediatric precursor B-ALL patients have different miRNA expression profiles than samples of normal bone marrow and CD34 þ sorted cells. 22 Moreover, miRNAs were significantly differentially expressed between T-ALL cases and normal thymocytes. 22 Cytogenetically relevant types of ALL in children display characteristic miRNA expression signatures as visualized in Figure 2 (adapted from Schotte et al 22 ).…”
Section: Aberrant Mirna Expression Characterizes Different Cytogenetimentioning
confidence: 99%
See 2 more Smart Citations
“…miR-155 was reported to be upregulated in patients with an internal tandem duplication of the FLT3 gene (19). Schotte et al showed that 14 miRNAs are upregulated (miR-128a, miR-142-3p, miR-142-5p, miR-150, miR181a, miR-181b, miR-181c, miR-193a, miR-196b, miR-30e-5p, miR-34b, miR-365, miR-582, and miR-708), and 5 downregulated (miR-100, miR-125b, miR-151-5p, miR-99a, and let-7e), in acute lymphoblastic leukemia cells compared with normal CD34 + cells (20). Upregulation of miR-181a and miR-335 has been observed in AML patients carrying CEBPA gene mutations (21,22).…”
Section: Introductionmentioning
confidence: 99%